NATO’s Post-Cold War Trajectory - Webber, M. author. aut Link
XIV, 280 p.
Keywords: Two decades since the watershed of the Cold War, this book investigates NATO's staying power. This book investigates how the Alliance has adapted and managed to attend to new roles and purposes through the lens of International Relations theory. The Alliance will continue, but will remain subject to ongoing crises and challenges of change.